The Development of Trade-Economic Relationsbetween Russia and the EU: Temporary Difficultiesor the Beginning of a Long-Term Crisis - V. N. Sumarokov; L. O. Marganiya (Мир новой экономики)
The article analyzes the problems and prospects of development of trade-economic relations between Russia and the EU. Since the collapse of the Soviet Union the European Union is trade partner number one for Russia, on the other hand, the Russian Federation is in different years is a third person or fourth most important trading partner for the EU. The author evaluates the development of mutual trade, considering the dynamics, the balance of products at the present stage. In addition, an assessment of investment cooperation of the Russian Federation with the countries of the European Union. Special attention is paid to the influence of political contradictions that have arisen in relations between Russia and the EU, and prospects for minimizing this negative influence.